2016
DOI: 10.1007/s13197-016-2349-y
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and non-volatile compounds in green tea affected in harvesting time and their correlation to consumer preference

Abstract: Current study was designed to find out how tea harvesting time affects the volatile and non-volatile compounds profiles of green tea. In addition, correlation of instrumental volatile and non-volatile compounds analyses to consumer perception were analyzed. Overall, earlier harvested green tea had stronger antioxidant capacity (*61.0%) due to the polyphenolic compounds from catechin (23,164 mg/L), in comparison to later harvested green teas (11,961 mg/L). However, high catechin content in green tea influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…A study analyzing aroma-active compounds in Kimchi during fermentation utilizing vacuum simultaneous steam distillation-solvent extraction/gas chromatography/mass spectrometry (V-SDE-GC-MS) reported the 9 sulfur containing compounds, and 6 garlic-like aroma related compounds. Their work reported that garlic-like aroma was the dominant flavor profile (Kim et al, 2016). This study also finds the sulfur-containing compounds as major volatile flavor compounds found in radish-based Kimchi, which is in agreement with previous work.…”
Section: Volatile Flavor Analysis Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A study analyzing aroma-active compounds in Kimchi during fermentation utilizing vacuum simultaneous steam distillation-solvent extraction/gas chromatography/mass spectrometry (V-SDE-GC-MS) reported the 9 sulfur containing compounds, and 6 garlic-like aroma related compounds. Their work reported that garlic-like aroma was the dominant flavor profile (Kim et al, 2016). This study also finds the sulfur-containing compounds as major volatile flavor compounds found in radish-based Kimchi, which is in agreement with previous work.…”
Section: Volatile Flavor Analysis Resultssupporting
confidence: 92%
“…Volatile aromatic flavor analysis conducted in food products involved in GC-MS analysis, yet the column used for GC was slightly different from study to study. Previous studies used different column such as RTX-5 Column in green tea (Kim et al, 2016), HP INNOWAX column in cheeses (Izco and Torre, 2000), HP-5 column in Kimchi (Kang et al, 2003). The column choice in this study may also have influenced the volatile flavor profile of two radish-based Kimchi.…”
Section: Volatile Flavor Analysis Resultsmentioning
confidence: 98%
“…Furthermore, several groups of non-volatile compounds are related to the flavour of green tea, including metallic ions, polyphenolic compounds, purine alkaloids, amino acids, nucleotides, carbohydrates, organic acids and others (Liang et al, 2008;Kim et al, 2017). Phenolic compounds are the main flavour components in tea, such as EGC, EC, EGCG and ECG (Wang & Ho, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…H-bond donors log P Molar refractivity No. of violations (-)-epicatechin 3,5-di-O-digallate (EC35G) [7] 594 14 9 3.16 141.986 4 Rutin [8] 610 16 10 -1.88 137.495 4 (-)- epigallocatechin gallate (EGCG) [9] 458 11 8 2.23 108.921 2 Apigenin glycoside [10] 578 12 6 1.86 144.558 4 Flavonol 3-O-D-glucoside (FOG) [11] 400 8 4 0.45 99.615 0 Myricetin 3-glucoside (M-G) [12] 480 13 9 -1.01 107.939 1 (-)- epigallocatechin (EGC) [13] 306 7 6 1.25 74.288 1 Kaempferol [14] 286 6 4 2.31 72.386 0 (-)-epicatechin gallate (ECG) [9] 442 10 7 2.53 107.256 1 (+)-catechin [9] 290 6 5 1.55 72.623 1 (-)-epicatechin (EC) …”
Section: Data Descriptionmentioning
confidence: 99%